Analysis of the relationship between abdominal aortic calcification and frailty in the middle-aged and older US population - Rena Rehemuding; Kaisaierjiang Kadier; Xinliang Peng; Pengfei Liu; Diliyaer Dilixiati; Aikeliyaer Ainiwaer; Xiaozhu Liu; Xiangtao Liu; Xiang Ma (Preventive Medicine Reports)
Background and Objective: Abdominal aortic calcification (AAC) is a marker of cardiovascular disease and is associated with increased mortality in middle-aged and older populations. However, its relationship with frailty remains unclear.Methods: Data were obtained from the 2013–2014 National Health and Nutrition Examination Survey. AAC was quantified using the Kauppila scoring system based on dual-energy X-ray absorptiometry. Frailty was assessed using the frailty index. Multivariable logistic regression models examined the association between AAC and frailty.Results: A total of 2987 adults aged ≥40 years were included. Compared to individuals with an AAC-8 score of 0, low-risk (AAC-8 score = 1–2; OR: 1.24; 95 % CI, 1.00–1.53) and high-risk AAC (AAC-8 score ≥ 3; OR: 1.83; 95 % CI, 1.03–3.23) were associated with higher odds of frailty. Similarly, mild to moderate AAC (0 < AAC-24 score ≤ 6; OR: 1.26; 95 % CI, 1.03–1.54) and severe AAC (AAC-24 score > 6; OR: 1.79; 95 % CI, 1.07–2.99) showed positive associations with frailty.Conclusions: Among middle-aged and older populations in the United States, there exists a positive correlation between AAC and frailty. Our findings suggest that the AAC score holds promise as a valuable tool for the early identification of frailty.